ADVICE AND DISSENT : Why America Suffers When Economics And Politics Collide - Blinder, Alan S
Argues that there is a cultural divide between economists and politicians that results in bad economic policy, with politicians using economic advice to bolster pre-conceived notions, and economists failing to take short-term human costs into account